A comparison of end-to-end and end-to-side anastomosis following rectosigmoid resection in ovarian cancer cytoreductive surgery. Issue 2 (February 2023) - Graham, Radha; Kotsopoulos, Ioannis C.
Abstract: Introduction: A rectosigmoid resection with anastomosis is a common component of cytoreductive surgery for ovarian cancer. Evidence from colorectal studies suggests that end-to-side anastomoses may be associated with fewer complications than end-to-end approaches, but these have not previously been compared in an ovarian cancer patient cohort. Materials and methods: Over a 51-month period, 239 patients underwent cytoreductive surgery for FIGO stage III/IV ovarian cancer. A rectosigmoid resection was performed in 79 (33.1%) with anastomosis in 59 (74.7%). Pre-operative and intra-operative factors associated with anastomotic leak, and post-operative complications were compared by anastomotic technique. Results: Anastomoses were end-to-end in 33 (55.9%) and end-to-side in 26 (44.1%) patients. There was a greater proportion of patients with a higher American Society of Anaesthesiologists score in the end-to-side group, but no other statistically significant differences in pre-or intra-operative factors between the groups. There were three (9.1%) cases of anastomotic leak in the end-to-end group, and no leaks in the end-to-side group, but the difference did not reach statistical significance. Both leaks were small, and successfully conservatively managed. There was no significant difference in rate of Clavien Dindo grade III/IV complications, although there was a higher rate of grade II complications following an end-to-side anastomosis (p = 0.036). There was no difference in length of stay, time to restarting chemotherapy, re-operation or 90-day mortality rate. Conclusion: There was no significant difference in major morbidity following end-to-end or end-to-side anastomosis. Prospective randomised trials specifically focussed in ovarian cancer are needed.